Toward unified molecular surveillance of RSV: A proposal for genotype definition - Goya, Stephanie (2020)
Background: Human respiratory syncytial virus (RSV) is classified into antigenic subgroups A and B. Thirteen genotypes have been defined for RSV-A and 20 for RSV-B, without any consensus on genotype definition. Methods: We evaluated clustering of RSV sequences published in GenBank until February 2018 to define genotypes by using maximum likelihood and Bayesian phylogenetic analyses and average p-distances. Results: We compared the patterns of sequence clustering of complete genomes; the three surface glycoproteins genes (SH, G, and F, single and concatenated); the ectodomain and the 2nd hypervariable region of G gene. Although complete genome analysis achieved the best resolution, the F, G, and G-ectodomain phylogenies showed similar topologies with statistical support comparable to complete genome. Based on the widespread geographic representation and large number of available G-ectodomain sequences, this region was chosen as the minimum region suitable for RSV genotyping. A genotype was defined as a monophyletic cluster of sequences with high statistical support (≥80% bootstrap and ≥0.8 posterior probability), with an intragenotype p-distance ≤0.03 for both subgroups and an intergenotype p-distance ≥0.09 for RSV-A and ≥0.05 for RSV-B. In this work, the number of genotypes was reduced from 13 to three for RSV-A (GA1-GA3) and from 20 to seven for RSV-B (GB1-GB7). Within these, two additional levels of classification were defined: subgenotypes and lineages. Signature amino acid substitutions to complement this classification were also identified. Conclusions: We propose an objective protocol for RSV genotyping suitable for adoption as an international standard to support the global expansion of RSV molecular surveillance.